The problem of the conception of philosophy in the framework of Buddhist thought, drawn from the interpretation of the Kalama Sutta attributed to Ananda - Quispe Huamani, Paul A. (2024)
This study analyzes the concept of philosophy inherited in the Western tradition based onthe ideas of the Greeks, as well as their influence on the culture. On the other hand, taking as a reference the Kalama Sutta, an ancestral text within the Theravada Buddhist tradition, we will try to show how, through a careful interpretation, a conception of philosophy can be elaborated in the light of the skepticism that, it is believed, is commonto both traditions.